Analysis of Upstream Citarum Watershed Flow Using Semi-Distributed Hydrology Model with SWAT - Chalid, Abdul; Nugraha, Adi Setya; Agung, Prasoni (ASTONJADRO, 2025)
The large conversion of forests’ areas that have a significant spatial impact on the area causes an increase in annual sediment rates that exceed 100 tons/km2. This build up of sediment has the potential to reduce the rivers capacity to handle large intensity rainwater. This research aims to find out how reliable the Semi-Distributed model with the Soil and Water Assessment Tool (SWAT). The SWAT model is when applied to the Upper Citarum watershed (UCW). The results of simulations carried out for one year showed a maximum flow discharge of 441 m3/sec and a minimum flow discharge of 2.15 m3/sec. However, based on existing water estimation post data, the maximum observed discharge value is 460 m3/sec and the minimum observed discharge is 4.06 m3/sec. After calibrating the discharge from the simulation results of the SWAT method with the observed discharge, we obtained quite good results with NSE value > 0.56, which value indicates that the SWAT model has good results. Meanwhile, the R value ≥ 0.79. In other words, the SWAT method of flow discharge modeling can be applied and can be one of the method choice for generating discharge in the UCW.